Impact of Serum Free Triiodothyronine level in Predicting the Degree of Myocardial Injury In Patients With Acute ST Segment Elevation Myocardial Infarction - Ullah, Mohammad; Hasan, Md Mehadi; Khalequzzaman, Md; Islam , Kazi Nazrul; Rahman, Md Mostafizur; Easmin, Tania (Cardiovascular Journal, 2023)
Background: Acute myocardial infarction is one of the leading causes of death across the world. Acute ST-segment elevation myocardial infarction (STEMI) occurs from occlusion of one or more coronary arteries that supply blood to the heart. This abrupt disruption of blood flow is due to plaque rupture, erosion, fissuring or dissection resulting in obstructing thrombus. This transmural myocardial ischemia results in myocardial injury or necrosis, systolic and diastolic impairment. The cardiovascular system is very sensitive to thyroid hormones and a wide spectrum of cardiac changes have long been recognized in overt thyroid dysfunction. In the form of free T3 (FT3) as biologically active thyroid hormone, has various effects on the cardiovascular system, including upregulating effective myocardial contractile function, decreasing systemic vascular resistance, as well as improving endothelial function and promoting angiogenesis. In severe illness of non-thyroidal origin, including acute STEMI, thyroid hormone system may be rapidly down regulated. So the decrease in FT3 level may lead to decreased cardiovascular protection in patients with AMI. Methods: Total 110 patients with STEMI were approached for this study according to the inclusion and exclusion criteria. Patient were divided into two groups- low serum FT3 level (<3.5 pmol/L) in group A and normal serum FT3 level ( >3.5 pmol/L) in group B. Results: Among 110 patients in our study 40 (36%) were in the low FT3 group ( Group A) and 70( 64%) were in normal FT3 group ( Group B). Serum troponin-I values were significantly higher in Group A (13.9±11.0 ) than in group B ( 9.7±8.9 ) with p value .027. Wall motion abnormality was present in 39(97.5%) Vs 60(85.7%) patients with p value 0.047. LVEF was significantly lower in group A (41.08±6.55) than group B (44.47±6.99) with a p value of .014. Conclusion: As Low FT3 level in acute STEMI was associated with significantly lower left ventricular ejection (LVEF) and higher levels of cardiac biomarker, preferably troponin I, inclusion of serum FT3 may be a predictor for myocardial injury in STEMI. Cardiovasc j 2023; 16(1): 32-39